# 02 Horizontal Translation

- Author:
- Jason Lee

## Instructions

Move the slider for a in the applet and answer the following questions based on your observations.

## y = ln(x - a)

## Question 2.1

How do we obtain the graph of y = ln(x - 3) from the graph of y = ln(x)?

## Question 2.2

How do we obtain the graph of y = ln(x + 4) from the graph of y = ln(x)?

## Question 2.3

The equation y = ln(x - a) can be seen as replacing the variable x in the equation y = ln(x) by the variable _____.

## Question 2.4

The graph of y = ln(x - a) passes through the origin O if a is equals to ____.

## Question 2.5

In terms of a, the equation of the asymptote to the graph of y = ln(x - a) is ______.